SCIENCE AND CHILDREN: APPROACHES TO SCIENCE EDUCATION IN INDIAN PRIMARY SCHOOLS - Nirmala M (CV. Fahr Publishing, 2024)
This study aims to investigate the implementation of inquiry‑based science education (IBSE) in Indian primary schools and to examine the role of culturally responsive pedagogy (CRT) in enhancing children’s scientific understanding, engagement, and curiosity. Using a library‑based research method, the study systematically reviewed peer‑reviewed journal articles, policy documents, and curriculum frameworks published within the last five years, focusing on primary school contexts in India. Data were collected through a structured literature search and analyzed using thematic synthesis, categorizing findings into themes such as teacher readiness, classroom resources, language diversity, and integration of culturally relevant practices. The results indicate that IBSE is widely advocated but inconsistently implemented due to constraints such as large class sizes, limited material resources, and inadequate teacher training. Furthermore, classrooms that integrate culturally relevant content and vernacular support demonstrate higher student engagement and better conceptual understanding. The study’s novelty lies in its combined focus on primary education, inquiry‑based pedagogy, and culturally responsive teaching within the Indian context, bridging gaps between policy recommendations and actual classroom practices. These findings contribute theoretical and practical insights for educators, policymakers, and curriculum developers, offering evidence‑based guidance to enhance science education in diverse and resource‑varied settings. In conclusion, the study highlights that effective primary science education requires the integration of pedagogical innovation with cultural contextualization, emphasizing the importance of teacher professional development, curriculum adaptation, and resource support to improve educational equity and learning outcomes in Indian elementary schools.